The cuckoo clock of doom - Stine, R. L. (New York : Scholastic, 1995)
When his father brings home an antique cuckoo clock that has a dangerous spell on it, Michael ignores his father's warning about touching it. Now horrible things are happening to Michael.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
4.0.
008-012.
008-012.
400
Keywords: Clocks and watches -- Juvenile fiction; Horror fiction